Characterization of TRIB2-mediated resistance to anti-cancer drugs - Santos, Marta Machado Pereira dos (2016)
Cancer results from the accumulation of multiple mutations and is characterized by deregulated cell mechanisms including cell growth, tissue invasion, angiogenesis and metastasis, being responsible for a large number of worldwide deaths. Malignant melanoma is the most aggressive type of human skin cancer, being just 5% of all skin cancer cases but accounting for over 80% of all skin deaths. This is primarily the result of melanoma being highly resistant to conventional chemotherapy. The PI3K/AKT signaling pathway is involved in many cell processes like survival, proliferation, growth and is one of the most mutated pathways in all human cancers, particularly in melanomas. FOXO3a, a transcriptional factor, is a crucial component of the PI3K/AKT pathway regulating the transcription of genes that promote apoptosis and cell cycle arrest. Following its activation, AKT negatively regulates FOXO3a, via phosphorylation, leading to FOXO3a export from the nucleus into the cytoplasm where it is ubiquitinated and is degraded. Consequently, if AKT is constitutively active, this enables a cancer cell to avoid apoptosis and to keep proliferating. The TRIB2 protein was discovered to be a FOXO3a repressor and is over expressed in many cancers although how TRIB2 mediates this effect is unknown. This project evaluates TRIB2 drug resistance to a dual PI3K/mTOR inhibitor BEZ235 in a clinically representative in vivo BEZ235 treatment model to confirm if our in vitro data (published and unpublished) correlates in a 3D in vivo model and demonstrates that AKT and TRIB2 interact in both in vitro cell models and in ex vivo clinical samples.